(untitled) (Communications in Computational Physics, 2010)
We consider the multi-scale modeling of the isothermal chemical vapor infiltration (CVI) process for the fabrication of C/SiC composites. We first present a microscopic model in which the preform is regarded as a two-phase porous media described by a dynamic pore-scale node-bond network during the fabrication process. We then develop a macroscopic model by a upscaling procedure based on the homogenization theory.